Виявлення ознак економічних злочинів у процесі досудового слідства - Савчук, Т. І.; Savchuk, T. I.; ORCID: http://orcid.org/0000-0001-8024-5136 (Право і безпека. – 2014. – № 3 (54). – С. 150-156, 2014)
Розкрито актуальність проблеми виявлення економічних злочинів під час досудового слідства. Визначено, що доказування складається з двох видів діяльності: практичної діяльності слідчого зі встановлення обставин вчинення злочину та пізнавальної (теоретичної), під час якої аналізуються, оцінюються отримані в ході практичної діяльності дані та приймається відповідне рішення. Висвітлено основні способи виявлення економічних злочинів у процесі досудового слідства, до яких віднесено: 1) виявлення нових злочинів під час проведення слідчих (розшукових), негласних слідчих (розшукових) та процесуальних дій; 2) виявлення нових злочинів під час аналізу та оцінки даних по кримінального провадження.

The author notes that the problems of detecting economic crimes during the pretrial investigation have remained unnoticed by scholars and therefore, they are to be solved. The objective of the paper is the isolation of characteristics and identification of the ways and methods of detecting economic crimes during the pretrial investigation. Special attention is paid to the fact that the features of such crimes are often found out by investigators during the preliminary investigation. It is emphasized that proof consists of two activities: practical activity of an investigator while detecting the circumstances of the crime commission and cognitive (theoretical), when obtained data during the practical activity is analyzed and evaluated and appropriate decision is made. The basic methods of detecting economic crimes during the preliminary investigation are elucidated. They include: 1) identification of new crimes during the investigation (search), secret investigative (search) and procedural actions; 2) identification of new crimes during the analysis and evaluation of data on criminal proceedings. Detection of the features of new crimes during the investigative (search), secret investigative (search) and procedural actions is practical activity of an investigator, carried out during the investigative or other procedural action, along with the collection and verification of evidence within the investigation of criminal proceedings. But detection of the features of new crime during the analysis and evaluation of data on criminal proceedings is the mental activity of an investigator directed on investigation of different information obtained during the investigative actions and proceedings; provided by the operative and search units and any other. The main investigative actions are singled out. During these actions the data containing elements of a new economic crime commission is set. Such actions include interrogations, searches, seizures and review of documents. The basic positions of detecting economic crimes while conducting these investigative actions are elucidated. It is indicated that to facilitate the detection of economic crimes’ features an investigator should have the primary economic knowledge and use the help of specialists in the field of economics.

Раскрыта актуальность проблемы выявления экономических преступлений во время досудебного следствия. Определено, что доказывание состоит из двух видов деятельности: практической деятельности следователя по установлению обстоятельств совершения преступления и познавательной (теоретической), во время которой анализируются, оцениваются полученные в ходе практической деятельности данные и принимается соответствующее решение. Освещены основные способы выявления экономических преступлений в процессе досудебного следствия, к которым отнесены: 1) выявление новых преступлений при проведении следственных (розыскных), негласных следственных (розыскных) и процессуальных действий; 2) выявление новых преступлений во время анализа и оценки данных уголовного производства.
Detection of economic crimes’ features in the process of pretrial investigation
Выявление признаков экономических преступлений в процессе досудебного следствия
Савчук, Т. І. Виявлення ознак економічних злочинів у процесі досудового слідства / Т. І. Савчук // Право і безпека. – 2014. – № 3 (54). – С. 150-156.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; досудове слідство; досудебное следствие; pretrial investigation; економічні злочини; экономические преступления; economic crimes; слідчі (розшукові) дії; следственные (розыскные) действия; investigative (search) actions